MARKET SHOCKS IN SALMON AQUACULTURE: THE IMPACT OF THE CHILEAN DISEASE CRISIS. (13th March 2018) - ASCHE, F.; COJOCARU, A.L.; SIKVELAND, M.
Abstract: Several studies indicate an integrated global market for salmon. However, there is increasing evidence of market segmentation for various seafood species. A disease crisis in Chile that reduced production by two-thirds provides a strong market shock that can shed light on how strongly integrated the salmon market is. Our results indicate that Chilean producers changed the product mix and export markets as a result of the disease shock. Yet, the relative prices remained constant, indicating a high degree of market integration. Moreover, Chilean prices are endogenous to the Norwegian price, indicating that prices are determined at the global market.